Using case studies to explore the external validity of 'complex' development interventions - Michael Woolcock (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Rising standards for accurately inferring the impact of development projects has not been matched by equivalently rigorous procedures for guiding decisions about whether and how similar results might be expected elsewhere. These 'external validity' concerns are especially pressing for 'complex' development interventions, in which the explicit purpose is often to adapt projects to local contextual realities and where high quality implementation is paramount to success. A basic analytical framework is provided for assessing the external validity of complex development interventions. It argues for deploying case studies to better identify the conditions under which diverse outcomes are observed, focusing in particular on the salience of contextual idiosyncrasies, implementation capabilities and trajectories of change. Upholding the canonical methodological principle that questions should guide methods, not vice versa, is required if a truly rigorous basis for generalizing claims about likely impact across time, groups, contexts and scales of operation is to be discerned for different kinds of development interventions.
Keywords: O1; B40; 330; case studies; external validity; complexity; evaluation